COVID-19's Effects on Inward Foreign Direct Investment and Earnings Management in Southern Africa's Development Community - Nathanael, Abraham Charles; Hamadi Hussein, Mariamu; Patrick Swai , Janeth (Disclosure: Journal of Accounting and Finance, 2025)
This study evaluates the impact of COVID-19 on both inward Foreign Direct Investment (FDI) and accrual-based earnings management (AEM) in 16 Southern African Development Community (SADC) countries, with a particular focus on Kenya and Tanzania. Principally, it analyzes FDI inflows before and during the pandemic, highlighting disparities and exploring how they exert financial pressure on firms, influencing their earnings management behaviors. Additionally, the study evaluates how COVID-19-induced economic adversities and host countries' financial interventions, particularly public debt management, moderated the relationship between pandemic-related challenges and FDI inflows. The study relied on secondary data as its primary data collection technique, employing a longitudinal design; the study covered a three-year pandemic period from Q1 2020 to Q4 2022, against a pre-pandemic benchmark from 2017 to 2019. Findings revealed a statistically significant difference in average FDI inflows between these two periods. COVID-19 pandemic also revealed a statistically significant decline of FDI inflows with public debt management effectively mitigating uncertainties and thereby stabilizing FDI.  Concurrently, the study revealed a weak link between COVID-19 and AEM and the absence of a relationship between FDI and AEM during the pandemic among non-financial firms in Kenya and Tanzania, likely because the pandemic disrupted normal economic patterns, weakening traditional relationships such as the sensitivity of financial reporting quality to macroeconomic influences.